2006
DOI: 10.1007/s11240-006-9116-0
|View full text |Cite
|
Sign up to set email alerts
|

Adventitious plant regeneration on leaf explants from adult male kiwifruit and AFLP analysis of genetic variation

Abstract: The present work reports on a study of plant regeneration carried out with callus from the leaf blades and petioles of field-grown male adult kiwifruit plants (Actinidia deliciosa (Chev.) Liang and Ferguson). The cultivars used were 'Tomuri' and clone A, a selected male plant grown in north western Spain. The best shoot induction conditions were obtained in 'Tomuri' leaf blades cultured in K(h) medium in the presence of 23 lM Zeatin and 0.1 lM NAA. Under these conditions, more than 80% of organogenic callus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 26 publications
1
16
0
6
Order By: Relevance
“…[8], Carya illinoiensis [9,48], Syngonium podophyllum [49], Agave fourcroydes Lem. [50], Elaeis guineensis [51] Actinidia deliciosa [52], and Phoenix dactylifera [53]. In Arabidopsis, 66.7% of the analysed regenerated plants showed at least one polymorphism [4], while for barley, the literature data is controversial, since Ruiz et al [6] found that somaclonal variation did not appear to be a very frequent event, while Bednarek et al [54] reported that all the regenerated plants showed at least one polymorphism with respect to the control plant.…”
Section: Discussionmentioning
confidence: 99%
“…[8], Carya illinoiensis [9,48], Syngonium podophyllum [49], Agave fourcroydes Lem. [50], Elaeis guineensis [51] Actinidia deliciosa [52], and Phoenix dactylifera [53]. In Arabidopsis, 66.7% of the analysed regenerated plants showed at least one polymorphism [4], while for barley, the literature data is controversial, since Ruiz et al [6] found that somaclonal variation did not appear to be a very frequent event, while Bednarek et al [54] reported that all the regenerated plants showed at least one polymorphism with respect to the control plant.…”
Section: Discussionmentioning
confidence: 99%
“…A close relationship between the type of explants, regeneration system, and the presence of somaclonal variation was detected in shoots regenerated from leaf callus [99].…”
Section: Molecular Markersmentioning
confidence: 79%
“…Most studies have used female kiwifruit, but there is one report for male kiwifruit 'Tomuri' (Prado et al 2007). That research showed an organogenic callus induction rate of !80%, with an average of 14 new shoots in the second subculture from leaf explants cultured in media supplement with zeatin and NAA.…”
Section: Discussionmentioning
confidence: 99%